KESADARAN HUKUM DALAM MEMBAYAR RETRIBUSI (STUDI KUALITATIF PADA PEDAGANG DI PASAR ALFA INDAH, PETUKANGAN UTARA, JAKARTA SELATAN) - Vizla Machdavie Kazhilla (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2022)
ABSTRACT This study aims to determine the legal awareness of traders in paying retribution at Alfa Indah Market, North Petukangan Village, and to find out what factors cause obedient and disobedient traders to pay retribution. The research method used is qualitative descriptive. Research time in May-June 2021. The data collection procedure was carried out by means of observation, interviews through informants and key informants, and to complete it, a documentation study was carried out. Interviews with 12 informants, namely market traders and 1 key informant, namely market retribution collectors. And carry out the confirmation process to an expert, namely a lecturer at the State University of Semarang. The findings of this research is that the legal awareness of traders in Alfa Indah market regarding paying market retribution can be seen that most of the traders already know the law related to Law No. 28 of 2009 concerning market retribution. The average trader also understands the contents related to the purpose and benefits of market retribution in accordance with Law No. 28 of 2009. In terms of legal attitude and legal behavior, most traders have complied with the regulation of paying market retribution. Although there are still traders who have not fully comply with these regulations. Then, the factor that motivates traders to pay market fees is the responsibility factor for obligations. Meanwhile, the factors that motivate traders are not aware of paying market levies, namely economic factors/income and education factors. Keywords: Legal Awareness, Regional Retribution, Market Retribution